PERILAKU SOSIAL BERPACARAN PESERTA DIDIK DI SMP NEGERI 1 LORE UTARA KABUPATEN POSO - Nurjanna; Samintang; Sri Dewi Lisnawaty (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) IAIN Palu, 2023)
Dating is a crucial aspect of adolescent development, but it often poses complex challenges and consequences. This study aims to investigate the dating-related social behavior of students at SMP Negeri 1 Lore Utara in Poso Regency. A qualitative descriptive approach was employed, involving in-depth interviews with students, input from teachers, and examination of relevant documentation. The study included three students engaged in dating relationships and one Counseling Teacher who frequently handled dating-related reports. The findings revealed that students at SMP Negeri 1 Lore Utara predominantly utilized social media as their primary means of communication in dating relationships and actively participated in discussions about shared interests. They also engaged in social interactions within the school environment, such as hand-holding and walking together in corridors. Physical interactions, including hand-holding, hugging, and light kisses, were observed among dating students, who also exhibited emotional intimacy through active listening and support. Peers and family played a significant role in shaping students' perceptions and behavior in dating relationships, influencing partner selection, intimacy levels, and conflict resolution strategies. This research underscores the importance of schools and parents in guiding and reinforcing religious, social, and moral values to students. The study's findings can serve as a basis for developing more effective teaching strategies and approaches that assist students in managing their dating-related social behavior.